Prototype Alat Pengendali Lampu dengan Perintah Suara menggunakan Arduino Uno Berbasis Web - Nurul Isna Ganggalia; Apri Junaidi; Fahrudin Mukti Wibowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The use of electric power for lights often less considered, a lot of lights are on continuously even though it's not used. As a result, a lot of electricity is wasted. This motivated researchers to create innovations of creating a light control system. The light controller system is designed to simplify and benefit the user. For this reason, researchers make light controllers on the web use voice commands that can be done anywhere and anytime using the internet. Making a prototype of a light control system with voice commands utilizes speech to text on the Web Speech API that converts sound into text, then it will be processed into a command of light controllers by the Arduino Uno microcontroller. The researcher used the prototype development method, where through 3 stages starting from Listen to Customer, Design and Building, and Test Drive Evaluations. The testing results are Internet speed and noise level affect the success rate on the use of light control using sound. At 9.9 Mbps internet speed has a success rate of 86% with response time 2.01 second, while at internet speed 1.9 Mbps has a success rate of 65% with response time 2.50 second. At the noise level of 34.5 dB room has a success rate of 86% with response time 2.02 second, while the noise level of 62 dB has a success rate of 72% with response time 2.21 second.